An analytic drain current model for long‐channel undoped gate stack surrounding‐gate MOSFETs including interface fixed charges. (12th April 2013) - Wang, Danghui; Zhang, Man; Han, Ru; Lu, Yuhao; He, Lu
SUMMARY On the basis of the exact solution of Poisson's equation and Pao–Sah double integral for long‐channel bulk MOSFETs, a continuous and analytic drain current model for the undoped gate stack (GS) surrounding‐gate (SRG) metal–oxide–semiconductor field‐effect transistor (MOSFET) including positive or negative interface fixed charges near the drain junction is presented. Considering the effect of the interface fixed charges on the flat‐band voltage and the electron mobility, the model, which is expressed with the surface and body center potentials evaluated at the source and drain ends, describes the drain current from linear region to saturation region through a single continuous expression. It is found that the surface and body center potentials are increased/decreased in the case of positive/negative interface fixed charges, respectively, and the positive/negative interface fixed charges can decrease/increase the drain current. The model agrees well with the 3D numerical simulations and can be efficiently used to explore the effects of interface fixed charges on the drain current of the gate stack surrounding‐gate MOSFETs of the charge‐trapped memory device. Copyright © 2013 John Wiley & Sons, Ltd.